ENGAGING SECONDARY SCHOOL STUDENTS IN PHOTOVOICE-BASED SELF-REFLECTION IN WRITING CLASSROOM - Sukmawanti, Yusnita (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2023)
Integrating photo voice-based self-reflection strategies with high school students enhances the engagement and significance of English classes. This approach encourages students to actively participate in writing activities, engaging secondary school students in photo voice-based self-reflection in writing classroom While previous studies have explored the use of photo voice in language learning, limited research addresses its role in mediating secondary students' reflection, specifically in writing narrative paragraphs. This case study, conducted in a Banyuwangi high school with 11th-grade Language Class students, employs qualitative methods. Data collection involves classroom observations, critical incident captures, in-depth interviews with audio transcripts, and document analysis. Four key findings emerge: uncertainty in pre-writing tasks, challenges during writing, the impact of feedback, and teacher empowerment. Photo voice emerges as a valuable mediator for student self-reflection, benefiting both students and teachers. Integrating photo voice into writing classes enriches the learning experience, fostering improved writing skills and overall personal growth.